A novel high-flux, thin-film composite desalination membrane via co-deposition of multifunctional polyhedral oligomeric silsesquioxane and polyoxometalate. (1st August 2019) - Amini, Mojtaba; Naslhajian, Hadi; Akbari, Ali; Farnia, S. Morteza F.; Jabbari, Esmaiel; Gautam, Sanjeev; Chae, Keun Hwa
Graphical abstract: A one-pot co-deposition method was developed to synthesize novel organic–inorganic nanocomposite membranes in forward osmosis (FO) process. Abstract: This work describes the synthesis of a novel organic–inorganic nanocomposite membrane via an efficient one-pot approach of co-deposition of octa-aminopropyl polyhedral oligomeric silsesquioxane hydrochloride salt (OA–POSS) and polyoxometalate (POSS–Mo36 ) onto a support membrane. The structure and morphology of the thin film nanocomposite (TFN) membranes were characterized by FT-IR spectroscopy, atomic force microscopy (AFM), energy-dispersive X-ray analysis (EDX), and scanning electron microscopy (SEM). In addition, the effect of POSS–Mo36 on the performance of the thin film nanocomposite (TFN) membranes was investigated in a forward osmosis (FO) process. Experimental results demonstrate the enhanced desalination performance of the synthesized as compared to thin-film composite (TFC) polyamide membranes.